Underlying Inborn Errors of Immunity in Patients With Evans Syndrome and Multilineage Cytopenias: A Single-Centre Analysis - Miano, Maurizio; Guardo, Daniela; Grossi, Alice; Palmisani, Elena; Fioredda, Francesca; Terranova, Paola; Cappelli, Enrico; Lupia, Michela; Traverso, Monica; Dell’Orso, Gianluca; Corsolini, Fabio; Beccaria, Andrea; et al. (Frontiers in Immunology, 2022)
Background: Evans syndrome (ES) is a rare disorder classically defined as the simultaneous or sequential presence of autoimmune haemolytic anemia and immune thrombocytopenia, but it has also been described as the presence of at least two autoimmune cytopenias. Recent reports have shown that ES is often a manifestation of an underlying Inborn Errors of immunity (IEI) that can benefit from specific treatments. Aims: The aim of this study is to investigate the clinical and immunological characteristics and the underlying genetic background of a single centre cohort of patients with ES. Methods: Data were obtained from a retrospective charts review of patients with a diagnosis of ES followed in our centre. Genetic studies were performed with NGS analysis of 315 genes related to both haematological and immunological disorders, in particular IEI. Results: Between 1985 and 2020, 40 patients (23 males, 17 females) with a median age at onset of 6 years (range 0-16) were studied. ES was concomitant and sequential in 18 (45%) and 22 (55%) patients, respectively. Nine/40 (8%) patients had a positive family history of autoimmunity. Other abnormal immunological features and signs of lymphoproliferation were present in 24/40 (60%) and 27/40 (67%) of cases, respectively. Seventeen out of 40 (42%) children fitted the ALPS diagnostic criteria. The remaining 21 (42%) and 2 (5%) were classified as having an ALPS-like and an idiopathic disease, respectively. Eight-teen patients(45%) were found to have an underlying genetic defect on genes FAS, CASP10, TNFSF13B, LRBA, CTLA4,STAT3, IKBGK, CARD11, ADA2, LIG4 . No significant differences were noted between mutated and non-mutated patients and between subjects with classical ES and the ones with other forms of multilineage cytopenias. Conclusions: This study shows that nearly half of patients with ES have a genetic background being in most cases secondary to IEI and therefore, a molecular evaluation should be offered to all patients